LAND PRICES, RESIDENTIAL SEGREGATION AND DISTRIBUTION OF EMPLOYMENT: AN APPLIED STUDY FOR THE CITY OF CALI: un estudio aplicado para la ciudad de Cali - Ipia Astudillo, Jeisson; Vivas Pacheco, Harvy (Sociedad y Economía, 2017)
The article analyzes the relation between the land prices, the distance to the centers of employment and the residential segregation in Cali. For the accomplishment of such purposes exploratory analyzes of spatial data were made using as a unit of analysis the districts. We identify centers and sub centers with mathematical methods, and calibrate of cubic spline function using assessed valuations and the job densities. The exploratory analyses suggest to specify spatial econometric models with the land prices (endogenous variable), employment distribution and residential segregation (regressors). In spite of the great importance of the traditional center, findings manifest the transition toward a multicentric structure in the city. The econometric estimates evidenced a differentiated pattern in the land prices with high values in longitudinal zone off city, low values in the periphery areas with relatively big distances to the job centers and that concentrate the poorest groups of the city.